2017
DOI: 10.1371/journal.pgen.1006328
|View full text |Cite
|
Sign up to set email alerts
|

Genetic loci associated with coronary artery disease harbor evidence of selection and antagonistic pleiotropy

Abstract: Traditional genome-wide scans for positive selection have mainly uncovered selective sweeps associated with monogenic traits. While selection on quantitative traits is much more common, very few signals have been detected because of their polygenic nature. We searched for positive selection signals underlying coronary artery disease (CAD) in worldwide populations, using novel approaches to quantify relationships between polygenic selection signals and CAD genetic risk. We identified new candidate adaptive loci… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 105 publications
(134 reference statements)
5
37
0
Order By: Relevance
“…Similarly, wound healing and blood coagulation categories, proposed by our evolutionary analysis in primates were also enriched in pleiotropic effects, highlighting that these genes are involved in multiple pathways and exhibiting the importance that these categories could have in the evolution of senescence, as predicted by the AP theory of aging. In agreement with our results, a recent study found that coronary artery disease loci are enriched in antagonistic-pleiotropic signals and suggests that natural selection may have maintained genetic variation contributing to cardiovascular disorders because of its beneficial effects in early life ( Byars et al. 2017 ).…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, wound healing and blood coagulation categories, proposed by our evolutionary analysis in primates were also enriched in pleiotropic effects, highlighting that these genes are involved in multiple pathways and exhibiting the importance that these categories could have in the evolution of senescence, as predicted by the AP theory of aging. In agreement with our results, a recent study found that coronary artery disease loci are enriched in antagonistic-pleiotropic signals and suggests that natural selection may have maintained genetic variation contributing to cardiovascular disorders because of its beneficial effects in early life ( Byars et al. 2017 ).…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with theoretical predictions from evolutionary biology and empirical evidence, 6 this study showed GnRH1, but not GnRH2, positively associated with IHD.…”
Section: Discussionsupporting
confidence: 90%
“…5 Genetic selection in favour of both fertility and ischemic heart disease (IHD) has been demonstrated. 6 Reproduction is driven centrally by gonadotropin-releasing hormone 1 (GnRH1) 7 likely driven by environmental factors to ensure optimal timing of reproduction. We used Mendelian randomization to estimate the causal effect of GnRH1 on IHD.…”
Section: Introductionmentioning
confidence: 99%
“…Applying theories from evolutionary biology, growth and reproduction would be expected to trade-off against longevity [ 49 ]. Consistent with this theory, evidence of genetic selection in favour of both fertility and CAD has recently been reported [ 50 ]. A recent Mendelian randomization study also found some indications that genetically-predicted higher follicle stimulating hormone, usually associated with higher androgen levels, was positively associated with CAD risk, but genetically-predicted higher anti-Müllerian hormone and higher risk of testicular dysgenesis syndrome, usually associated with lower androgen levels, were negatively associated with CAD risk [ 51 ].…”
Section: Discussionmentioning
confidence: 53%